IMPORTANCE OF IMPLEMENTATION AND ENFORCEMENT OF HUMAN RIGHTS IN INDONESIA NOW - Alex Chandra; Supot Rattanapun (Sekolah Tinggi Ilmu Hukum Awang Long, 2023)
There are still many human rights violations in Indonesia, starting from the lightest to the most serious in the implementation of human rights, and there is no mechanism for handling these human rights. From this research using literature review which aims to learn from existing references to understand the meaning of human rights and apply the values of Pancasila which contain the values of civilized human principles because they are the enforcement of human rights in civic life so that students can appreciate it more. the rights of everyone by not violating human rights. This human right has the power of fundamental or fundamental power. Currently, there are violation cases that have occurred because many people still do not understand the violation cases so that it is easier for people to violate the rights of others. Protection and maintenance of human rights within a national institutional framework is established in an institution such as the Indonesian Child Protection Commission (KPAI), the National Commission for Women (Komnas Perempuan), the National Commission on Human Rights (Komnas HAM), and the Truth and Reconciliation Commission (KKR), was dissolved because the KKR might not be responsible and did not carry out its function properly. Currently, human rights law enforcement is carried out specifically through the judiciary, whose Human Rights Courts target serious human rights courts, and which have the authority to test the 1945 Constitution, namely the constitutional court. These rights are largely upheld by the Constitutional Court, and many unlawful decisions have been made. This decision has strategic value, so that it can protect the human rights of citizens.